STRATEGI PENINGKATAN MUTU PENDIDIKAN DI MADRASAH ALIYAH NEGERI MUARA ENIM - Solehan Solehan (Conciencia, 2014)
AbstractThis thesis titled "Strategies for Quality Improvement of Education in Madrasah Aliyah Muara Enim" This thesis is motivated by the demand for quality educational institutions that can create quality human resources. Madrasah Aliyah Muara Enim, one - the only state school madrasah aliyah in the district of Muara Enim required role to be able to realize these expectations.This study uses descriptive qualitative approach. Data retrieved through observation, interviews and documentation. Respondents consisted of the headmaster, the deputy headmaster, head of TU, head of the library and a few teachers. The focus of research is how the strategy of improving the quality of education in Madrasah Aliyah Muara Enim? factors that are enabling and inhibiting? Bagamainana efforts in improving the quality of education.The results show that the strategy undertaken to improve the quality of education in Madrasah Aliyah Muara Enim is enhancing the quality of teachers, improvement of academic and non academic achievement, performance improvement and achievement of the National Examination Exams value and increased infrastructure. Contributing factor in improving the quality of education is largely qualified educators S1 according to the subject of teaching, madrassas have educational programs and a clear division of labor, infrastructure, and environment conducive climate and great support from the Government of Muara Enim and PT Bukit Asam Tanjung Enim. Inhibiting factor is the low student motivation, employee resource is not maximized, the low level of discipline teachers and the availability of funds is still lacking. Efforts are being made in improving the quality of education is to intensify the activities of guidance and counseling, creating a learning environment that is attractive, giving awards to outstanding students, enroll the employee in training activities, cooperation with donors and implementing electrical attendance system for teachers and employees. Keywords: Strategies and Quality of Education.